Redifferentiated Chondrocytes in Fibrin Gel for the Repair of Articular Cartilage Lesions. Issue 10 (August 2019) - Bianchi, Vanessa J.; Lee, Adrienne; Anderson, Jesse; Parreno, Justin; Theodoropoulos, John; Backstein, David; Kandel, Rita
Background: Autologous chondrocyte implantation, which uses passaged chondrocytes, commonly leads to the formation of fibrocartilage. When chondrocytes are passaged to increase cell numbers, they lose their phenotype and ability to form hyaline cartilage. The use of transforming growth factor β (TGFβ) to redifferentiate passaged chondrocytes has been validated in vitro; however, it is unknown if redifferentiated chondrocytes will enhance defect repair when implanted in vivo. Furthermore, fibrin gel is used in orthopaedic surgery as a fixative and scaffold and could be an appropriate carrier to enhance retention of cells in the repair site. Purpose: To investigate if passaged redifferentiated chondrocytes in fibrin gel have the ability to form cartilage tissue and if these redifferentiated cells will enhance the formation of hyaline cartilage in vivo when implanted into critical-size osteochondral defects. Study Design: Controlled laboratory study. Methods: Rabbit and human chondrocytes were serially passaged twice in monolayer culture. Twice-passaged cells were used directly (dedifferentiated) or redifferentiated in high-density culture with TGFβ3. Dedifferentiated or redifferentiated cells were mixed with fibrin gel to form fibrin clots, which were cultured in vitro to assess the use of fibrin gel as a scaffold or implanted in vivo in a critical-size osteochondral defect in New Zealand White rabbit knee joints. Rabbits were sacrificed 6 weeks after implantation, and tissues were assessed histologically and by immunohistochemistry. Results: Redifferentiation of passaged chondrocytes by means of 3-dimensional culture in the presence of TGFβ3 improved the formation of cartilaginous tissues in vitro, and culture in fibrin gel did not affect the cell phenotype. Implantation of dedifferentiated cells in vivo resulted in fibrocartilaginous repair tissues. Redifferentiated chondrocyte implants resulted in granulation tissues containing the hyaline cartilage marker collagen type 2. Conclusion: Redifferentiated chondrocytes will maintain their chondrogenic differentiation in fibrin clots. Implanted redifferentiated chondrocytes show a different reparative response than dedifferentiated chondrocytes and do not appear to enhance repair at an early time point. Another study of longer duration is required to assess tissue maturation over time. Clinical Relevance: Redifferentiation of passaged chondrocytes with TGFβ3 before implantation does not improve defect repair in the first 6 weeks.